Macroprudential policy in a recovering property market: too much too soon?. Issue 4 (1st October 2016) - Duffy, David; McInerney, Niall; McQuinn, Kieran
Abstract : The aftermath of the 2007/2008 financial crisis has resulted in many central banks and regulatory authorities examining the effectiveness of macroprudential policy in preventing the emergence of future credit bubbles. Specific limits on loan-to-value (LTV) and loan-to-income (LTI) ratios have been introduced in a number of economies as a means of ensuring greater financial stability. The Irish property and credit market were particularly affected in the crisis as the domestic housing market had, since 1995, experienced sustained price and housing supply increases. Much of the activity in the Irish market was fuelled by a credit bubble following the emergence of international wholesale funding post 2003. After a period of pronounced declines, Irish house prices in late 2013 started to increase significantly; in early 2015, in response, the Irish Central Bank imposed new LTV and LTI limits to curb house price inflation. However, the introduction of these measures comes at a time when housing supply and mortgage lending are still at historically low levels. Therefore, in this paper we use a newly developed structural model of the Irish property and credit market to examine the implications of these measures for house prices and key activity variables in the mortgage market.